Profile of chronic renal failure patients on hemodialysis treatment in a regional hospital in southern Pará, Brazil (Research, Society and Development, 2022)
Introduction: Chronic renal failure (CRF) is a syndrome that causes the progressive and irreversible loss of kidney function, and its treatment is considered of high cost to the public health system. The growing incidence of chronic kidney disease (CKD) is due to the increase of some chronic degenerative diseases, especially systemic arterial hypertension (SAH) and diabetes mellitus (DM).  Objective: To describe the profile of chronic renal failure patients undergoing hemodialysis treatment in a regional hospital in southern Pará (Brazil). Methodology: This is a descriptive, cross-sectional, quantitative study. We used a survey of data available in the electronic system / records of patients undergoing hemodialysis treatment in a regional hospital in southern Pará. Results: The studied population was composed of 91 patients. Regarding the CKD etiology analysis, we identified a predominance of SAH (39.56%) and DM (30.76%). As for laboratory parameters, the results were analyzed in relation to the goals established for quality in hemodialysis by the ordinance No. 389/14. Conclusion: With the identification of the profile of renal patients, it is expected to contribute to the improvement of strategies for the promotion and prevention of population health.